Peer-induced quiescence of male Drosophila melanogaster following copulation - Lynn, Katrina; Ichinose, Toshiharu; Tanimoto, Hiromu (Frontiers in Behavioral Neuroscience, 2024)
Mating experience impacts the physiology and behavior of animals. Although mating effects of female Drosophila melanogaster have been studied extensively, the behavioral changes of males following copulation have not been fully understood. In this study, we characterized the mating-dependent behavioral changes of male flies, especially focusing on fly-to-fly interaction, and their dependence on rearing conditions. Our data demonstrate that male flies quiesce their courtship toward both females and males, as well as their locomotor activity. This post-copulatory quiescence appears to be contingent upon the presence of a peer, as minimal variation is noted in locomotion when the male is measured in isolation. Interestingly, copulated males influence a paired male without successful copulation to reduce his locomotion. Our findings point to a conditional behavioral quiescence following copulation, influenced by the presence of other flies.